Peran Kepala Sekolah dalam Mendukung Pemanfaatan Kecerdasan Buatan (AI) oleh Guru untuk Pengembangan Pembelajaran di Sekolah Menengah Pertama - Kholidin Kholidin; Karmiati Karmiati; Khaedar Abdussofi; Khaerul Umam Muttaqin; M. Nur Iskandar; Suparjo Suparjo (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to identify the role of school principals in supporting teachers’ use of Artificial Intelligence (AI) for developing Deep Learning Lesson Plans in junior high schools, analyze how such support influences teachers’ competencies, and develop a relevant training program model to enhance teachers’ utilization of technology. This research employed aqualitative approach with a case study design, involving school principals and teachers from schools that have integrated educational technology. Data were collected through in-depth interviews, classroom observations, and document analysis including s and school policies. Research instruments consisted of semi-structured interview guides and observation notes, while data validity was strengthened using triangulation techniques. Thematic analysis was applied to identify key patterns related to the principal’s support in AI implementation. The findings show that school principals play a strategic role in six key areas: technology facilitation, professional guidance, linkage to learning resources, implementation supervision, teacher innovation encouragement, and school policy management. Principal support significantly enhances teachers’ motivation and competence in using AI to develop more creative, data-driven, and student-responsive s. Furthermore, systematic training and mentoring provided by principals strengthen teachers’ confidence in integrating technology into their instructional practices. The leadership role of school principals that specifically integrates strategic, pedagogical, and policy support in the utilization of artificial intelligence (AI) for the development of Deep Learning Lesson Plans at the junior high school level. Overall, this study highlights the importance of visionary school leadership in optimizing the use of AI to improve learning quality.